UNDERSTANDING THE EXPERIENCES AND CHALLENGES OF NEWLY GRADUATED NURSES IN TRANSITION TO PRACTICE - Turki Fahad Al Dawsari, ‏Haya Saeed Alshahrani, ‏Najoud Yahyia Alzahrani, ‏Abdullah Ahmed Otayf, ‏Ali Yahya Alqahtani, ‏Fatimah Hadi Hadadi, ‏Muneif Amer Aldawsari, ‏Salma Hulel Alotaibi, ‏Zahera Mshlah Alasifer, ,; Khaled Hamoud Al Sofayany, ‏Abdulrahman Ibrahim Alhomidi, ‏Fatimah Hassan Ghzwani, ‏Ebtesam Obeed Almeteeri, ‏Reem Mohammed Maaidi, ‏Faizah Mazeal Aldaferi, (Chelonian Research Foundation, 2022)
The transitional issues that newly graduated nurses (NGNs) face when they begin their nursing careers are summarized in this overview. Achieving a healthy work-life balance is a challenge, and there are many obstacles to overcome during the transition from student to practicing nurse, such as a mismatch between theoretical knowledge and practical experience, communication problems, time management issues, and ethical challenges. The dynamic and unpredictable character of clinical practice—which might differ greatly from the controlled settings of nursing education programs—is the root cause of these challenges. Overcoming these obstacles requires a multifaceted strategy that includes mentoring, education, and organizational assistance. The goal of nursing education programs should be to close the knowledge gap between theory and practice by providing NGNs with lots of opportunity to practice and gain practical experience in clinical settings. Initiatives for mentorship are essential in helping NGNs feel competent and confident in their work by offering them advice and assistance. Healthcare organizations should also put policies in place to support work-life balance, offer continuing education and training, and foster a courteous and cooperative work environment. Stakeholders may help NGNs transition into the nursing profession more smoothly by acknowledging and addressing the particular difficulties they confront. This will ultimately help to build a workforce of qualified and resilient nurses. Keywords: Newly Graduated Nurses, Challenges, Experiences, Healthcare.